MENINGKATKAN KREATIVITAS ANAK MELALUI MEDIA BAHAN ALAM DI TAMAN KANAK-KANAK SUSTER PONTIANAK KOTA - Rupini Rupini; Muhamad Ali; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study was aimed to increase the creativity of children aged 5-6 years through the use of learning media from natural materials at Taman Kanak" Suster Pontianak. This research was used the action research method of the Kemmis Taggart model. Qualitative data were analyzed using inductive processes with data reduction and data presentation, meanwhile the quantitative data were analyzed by using the formula for calculating average scores and percentages to see the comparison of each cycle. The subjects of this research was children of group B1 (5-6 years old) totaling 26 children consisting of 13 women and 13 men. Data collection techniques used in this research were the observation sheet and documentation, meanwhile the data collection tool was the child's observation sheet. Research findings: 1. There were differences in the overall percentage of each cycle and in each cycle there was a consistent increase, 2. Children's creativity can be increased through the use of learning media from natural materials. The implication is that teachers should be able to use learning media from natural materials that are around the school to develop children's creativity. Keywords:Creativity, Learning Media, Natural Material Media